Evaluating Prevalence of Postural Changes in Freestyle and Greco-Roman Wrestlers: A Review of Literature - Ali Asghar Norasteh; Rasoul Bayati (Islamic Azad University, Hamedan Branch, 2021)
Objective: Intense training and competition lead to fatigue and muscular imbalance in wrestlers that cause postural abnormalities. Thus, it is essential to identify these changes and the related mechanisms to prevent musculoskeletal and sports injuries among wrestlers. The present study is a comprehensive review of the literature on postural changes in freestyle and Greco-Roman wrestlers. Methods: This paper offers a thorough review of the literature on changes in freestyle and Greco-Roman wrestlers. It encompasses a series of search queries from inception to Mar 2020 from existing databases including PubMed/MEDLINE, EBSCO Web of Science, Science Direct, Cochrane Central Register of Controlled Clinical Trials, Google Scholar, and Scopus. A host of other publications were also reviewed manually. Once candidate papers were extracted, the title and abstract were studied, those meeting the inclusion criteria were selected for further analysis, and the others were discarded.  Results: A total number of 11 articles were selected. Overall, 4 articles studied postural changes in wrestlers, 2 studied Q angle and flat foot, and 5 compared the two wrestling styles. Conclusion: Results show that estimated changes in kyphosis, lordosis, forward shoulder, forward head, Q angle, and flat foot were more significant among wrestlers. However, the kyphosis angle was higher among freestyle wrestlers, while a higher lordosis angle was observed for Greco-Roman wrestlers. Moreover, a higher degree of flat foot and Q angle was observed in the dominant leg of experienced freestyle wrestlers. Results of forwarding shoulder and forward head were contradictory, and more studies need to be done.